Multi-million-year magmatic and hydrothermal activity is key to the formation of supergiant to behemothian porphyry copper deposits - Adrianna Luiza Virmond; Jörn-Frederik Wotzlaw; Rodrigo Rojas-Arancibia; David Selby; Cyril Chelle-Michou (Contributions to Mineralogy and Petrology, 2024)
Understanding the primary controls on mineral deposit formation and size is essential for sourcing the metals required by our ever-growing economy. The tonnage of porphyry copper deposits ranges five orders of magnitude but the key mechanisms and processes that modulate the size of these deposits remain enigmatic. Here, we investigate the behemothian deposits of the Chuquicamata Intrusive Complex (CIC) in northern Chile employing high-precision U–Pb and Re–Os geochronology. We resolve a complex long-lived magmatic-hydrothermal activity that lasted over 3.3 Myr. High-precision zircon petrochronology data indicate two distinct porphyry emplacement episodes, separated by 0.5 Myr, with the younger generation closely tied to the main intervals of hydrothermal mineralization. High-precision Re–Os molybdenite dates reveal a prolonged hydrothermal mineralization interval (> 2.5 Myr) that progressively migrated southwards within the CIC and continued after the end of the (apparent) magmatic activity. We show that the rate of copper precipitation varies little in nature (0.025–0.10 Mt/kyr) and is independent of the size of the deposit. Consistent with evidence from smaller deposits, our findings provide unprecedented evidence that copper endowment in porphyry copper deposits positively correlates with the timescales of magmatic and hydrothermal activity. Supergiant to behemothian deposits require multi-million-year magmatic-hydrothermal activity, linking the largest porphyry copper systems to a simple metric – the duration of magmatic-hydrothermal activity.